Effect of extreme weather events on child health in rural Uganda - Emily Injete Amondo; Alisher Mirzabaev; Emmanuel Nshakira Rukundo (University of Bonn, Center for Development Research (ZEF), 2021)
Children in rural farming households across the developing countries are often vulnerable to a multitude of risks, including health risks associated with climate change and variability. This study empirically traced the effect of extreme weather events on nutritional health outcomes among rural children in Uganda, while accounting for households' behavioural responses. We combined four waves of the Uganda National Panel Survey (UNPS) for the period 2009-2014, with long-term rainfall and temperature datasets and study the effect of extreme weather shocks on child health. We find that droughts and heat waves worsened child anthropometrics, particularly child chronic undernutrition. Exposure to drought significantly lowered height-for-age scores (HAZ) of up to -0.57 standard deviations. The main causal transmission channels were through lower crop production and increased frequency of child diseases. We highlight on the importance of ex-ante resilience building against extreme weather events particularly when compared to ex-post relief actions.
Keywords: I13; I15; I18; J0; 330; Child health; droughts; Uganda